The investigations of a peculiarities of pyrocarbon gas phase densification of powders of the catalytic carbon formations (CCFS), obtained on nickel - Fursov, S.G.; Gujda, V.V.; Lyashenko, S.A.; Meltyukhov, M.V.; Aulova, O.S. (Вопросы атомной науки и техники, 2021)
Investigations on gas-phase densification of the catalytic carbon formations (CCFs), obtained on nickel, using the method of radially driven pyrolysis zone were carried out. Straight dependence of the brittle strength of the CCFs, bonded with pyrocarbon (CCFBPyC), from the CCFs morphology, was shown. It was determined, that the result of decreasing of an amount of fibrous, fine-grained CCFs component is the increasing of strength of the pyrocarbon matrix . For the first time, carbon/carbon composite materials (CCCM ) without cracks, which contain refined or not-refined from nickel, carbon nanomaterials (CNM), were obtained.